THE MOTIVATIONAL COMPONENT OF POSTGRADUATE EDUCATION LECTURERS’ PERSONAL READINESS TO WORK AT CHANGES - Levsheniuk, Natalia (PSYCHOLOGICAL JOURNAL, 2020)
The article describes peculiarities of the motivational component in the structure of a postgraduate education lecturer’s readiness to work at changes. The problem of the development of postgraduate education lecturers’ motivation to professional work in the conditions of social changes is discussed. The set of factors that influence the motivational behaviour are identified and described, namely, they are: lecturers’ needs, motives, interests, goals and incentives. The experimental research has identified motives that are important for postgraduate education lecturers: social, pragmatic, prestigious, professional, personal or professional self-improvement motives. Different indicators of postgraduate education lecturers’ personal readiness should be developed depending on their organizational, professional, age and gender characteristics, which was determined with the analysis of variance. Insufficient work motivation of postgraduate education lecturers within their personal readiness was determined in general and depending on their gender-age and organizational and professional characteristics, in particular. The obtained experimental data suggest that postgraduate educational institutions must prepare their employees to be ready to work in changing working conditions. In the addition to meeting the lecturers’ pragmatic needs, it is necessary to give them opportunities and to reveal hidden resources of their Self and personal self-improvement. Thus, a corrective program should be developed for postgraduate education lecturers as an auxiliary method increasing the motivational component of their personal readiness.